Development of Butterfly Pea-Aloe Vera Mouthwash with Antimicrobial Activity Against Streptococcus mutans - Boonkasemsin, Charuporn; Arpornrat, Jidapha; Angwarawong, Thidarat; Klanrit, Poramaporn; Angwaravong, Onauma (Khon Kaen University Dental Journal, 2025)
Objective: Dental caries is the most common oral health issue in the Thai population, primarily caused by Streptococcus mutans (S. mutans). Although chlorhexidine (CHX) mouthwash is the gold-standard antibacterial agent for reducing dental plaque and pathogenic microorganisms such as S. mutans, it is associated with side effects such as tooth discoloration, altered taste, dry mouth, and oral burning sensations. Consequently, plant-based extracts are increasingly being explored as safer alternatives. Previous studies have demonstrated that both Butterfly pea and Aloe vera possess antibacterial activity against S. mutans; however, no study has evaluated the efficacy of a Butterfly pea–Aloe vera solution. Therefore, this study aims to assess the effectiveness of Butterfly pea-Aloe vera solutions against S. mutans. Materials and Methods: To evaluate the antimicrobial effect of Butterfly pea–Aloe vera solutions against S. mutans, thirteen groups were tested using a modified broth dilution assay and the drop plate technique. These groups included three Butterfly pea solutions at 400 (BP400), 200 (BP200), and 100 mg/mL (BP100); three Aloe vera solutions at 100 (AV100), 50 (AV50), and 25 mg/mL (AV25); four formulations of Butterfly pea–Aloe vera solutions (BP200_AV50, BP200_AV25, BP100_AV50, BP100_AV25); a bacterial suspension (experimental control); CHX (positive control); and deionized water (DI, negative control). Colony-forming units (CFU/mL) were analyzed using the Kruskal–Wallis and Mann–Whitney U tests (a=0.05). Results: All Butterfly pea solutions (BP400, BP200, BP100) and combined Butterfly pea–Aloe vera solutions (BP200_AV50, BP200_AV25, BP100_AV50, BP100_AV25) significantly inhibited S. mutans compared to the DI group, with no significant difference between the Butterfly pea group and the Butterfly pea–Aloe vera group. All Aloe vera solutions (AV100, AV50, AV25) showed no significant inhibition and performed similarly to the DI group. The CHX group exhibited the highest antibacterial activity. Conclusion: Butterfly pea solution at 100 mg/mL and the Butterfly pea–Aloe vera solution at BP100_AV25 show promise as natural alternatives to chemical-based mouthwashes for daily caries prevention. Further development will focus on BP100_AV25 as a ready-to-use, chemical-free herbal mouthwash, aiming to harness additional biological properties of the two plants, such as anti-inflammatory, wound-healing, and remineralization effects.